Gestión del programa nacional de saneamiento rural y su influencia en la calidad de vida en el centro poblado Cahuide distrito de San Juan Bautista 2024 - Meléndez Cambunungui, María de los Angeles (2025)
The main objective of this report was to determine the management of the National Rural Sanitation Program and its influence on the quality of life in the Cahuide Population Center, San Juan Bautista District 2024. Using a basic explanatory level method with a non-experimental design. Taking 250 families as a sample, to whom a questionnaire was applied to collect information. After analyzing the results, the management of the Rural Sanitation P.N is considered deficient (40%); while the quality of life in the Population Center is rated as bad (32%). Specifically, program management explains 84.6% of the variability in quality of life (R² = 0.846), sanitation accessibility 50.6% (R² = 0.506), sustainability 32.7% (R² = 0.327), public health 23.4% (R² = 0.234), staff capabilities 77.0% (R² = 0.770), and management efficiency 31.8% (R² = 0.318). In addition, both staff capabilities and health education also contribute significantly, with an R² of 0.770, indicating that both factors are determinants of population well-being.